2008
DOI: 10.1186/1471-2148-8-298
|View full text |Cite
|
Sign up to set email alerts
|

A homogenous nature of native Chinese duck matrilineal pool

Abstract: BackgroundChina, with around 30 unique breeds, has a diverse duck genetic pool. Currently, there is no systematic report which investigates the genetic diversity, phylogenetic relationship, and matrilineal genetic structure of these domestic breeds and wild mallards (Anas platyrhynchos).ResultsIn this study, we sequenced the mitochondrial DNA (mtDNA) control region segments in 278 domestic ducks (Anas platyrhynchos domestica) from 19 indigenous breeds/populations and 70 wild mallard samples and analyzed them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…They only determined 4 haplotypes among 70 samples, the two minor haplotypes (H3 and H4) differed from the main type (H2) only by one-mutation distance, haplotype 1 contained 3 individuals which retrieved from Genbank and had also only one mutation distance without counting the transversion variations. This pattern of low genetic variability and simple haplotype components was similar to the study of domestic duck origin in China, which found that the matrilineal pool of Chinese domestic ducks and mallards was homogeneous without clear geographic differentiation [8].…”
Section: Introductionsupporting
confidence: 58%
“…They only determined 4 haplotypes among 70 samples, the two minor haplotypes (H3 and H4) differed from the main type (H2) only by one-mutation distance, haplotype 1 contained 3 individuals which retrieved from Genbank and had also only one mutation distance without counting the transversion variations. This pattern of low genetic variability and simple haplotype components was similar to the study of domestic duck origin in China, which found that the matrilineal pool of Chinese domestic ducks and mallards was homogeneous without clear geographic differentiation [8].…”
Section: Introductionsupporting
confidence: 58%
“…Amplification of DNA was performed by using a thermo cycler machine on the cyt b mtDNA using forward primer (TGCAACCCCAGTCCTAGTC 5'-3'), and reserve primer (GAAGGCTAGGATTTT GCGTGT-3'-5'). The design of oligonucleotide specific primer of cytochrome b gene was performed on the basis of the database of GeneBank EU678239.1 (He et al, 2008 Furthermore, the PCR product were separated by electrophoresis in 1.5% low-melting agarose gel using 0,5 TBE buffer in electrophoresis machine Power PAC 3000 (BIO PAD).…”
Section: Isolation Of Dna and Amplificationmentioning
confidence: 99%
“…With the development of DNA sequencing techniques and extensive use of mtDNA molecular marker in studies on animal population genetic structure and systematic evolution, more and more studies have recently been reported on the genetic diversity, genetic differentiation and origin of chickens (Liu et al, 2006;Song et al, 2007;Zhu et al, 2009), ducks (He et al, 2008;Li et al, 2010) and geese Li and Wang, 2007;Zhu et al, 2010), as well as other poultry by using mtDNA markers. However, there has been no systematic and precise report on genetic diversity and maternal origin of Chinese black-bone chicken using mtDNA molecular markers.…”
Section: Introductionmentioning
confidence: 99%